Adsorption of cadmium by using regular Zn-AlC0₃ hydrotalcite / Zuritah A.Kadir - A.Kadir, Zuritah (Faculty of Applied Sciences, 2009)
Heavy metals pollution is very serious problem in waste water pollution around industrial area. In this study, Zn-AlCO₃ LDH was investigated as an alternatively low-cost adsorbent for the adsorption of cadmium in aqueous solution. Zn-AlCO₃ LDH with ratio 4 was synthesis by co-precipitations method at room temperature. X-Ray Diffractometer (XRD) pattern showed the presence sharp peaks, signifying high crystallinity with d₀₀₃ of 7.63 Å which demonstrated general features of LDHs phase without impurity phase. The different parameters that affect the adsorption process were studied included contact time, temperature, adsorbent dosage, initial concentration and pH. The optimum contact time was 120 minutes with 40 mg/L initial concentration. The percentage uptake of cadmium increases with initial concentration, adsorbent dosage and temperature. The optimum pH obtained was at pH 7. For the Adsorption isotherm, the Langmuir isotherm more fitted to the experimental data with R² value of 0.877.